The Online Social Media Marketing Affecting the Decision to purchase Clothing via Facebook live of customer in Lung Prabang - MANEVONG, Seng a thith; SOMSAMONE, Vilayphone; SENGKEO, Phonesouda; KHATTIGHALATH, Lithigha (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
Technology information has been improved that leads to change the living condition and the business toing must follow the online marketing through facebook live to meet the demamd of the buyers as well as the target consumers. The on live marketing also facilitate sale promote their products easier. To study on The Online Social Media Marketing Affecting the Decision to purchase Clothing via Facebook live of customer in Lung Prabang, which is a quantitative analysis and have research Objective: 1) The Online Social Marketing Affecting the Decision to purchase Clothing via Facebook live of customer in Lung Prabang and 2) The behavior of Decision to purchase Clothing via Facebook live of customer in Lung Prabang by questioning and surveyed 323 buyers. The data was analyzed by the Pearson Product Moment Correlation Ceofficient and Stepwise Multiple Regression Analysis. The Online Social Marketing Affecting the Decision to purchase Clothing via Facebook live of customer in Lung Prabang consist of five factors such as: the interaction, Word of Mouth, Trust, System Quality, Data Quality and Service Quality in statistical significance at the level of 0.1. The behavior of Decision to purchase Clothing via Facebook live of customer in Lung Prabang shows that Frequency of using the online network to buy clothes is once a week which worthless than 100,000 kip with an average of 500,00 kip per purchase because it’s either for the buyer to do so with the payment on BCEL one program. The other factor is friend has more power to make the buyer making decision to buy clothes with special promotion such as deduction, giving for free.